Pelatihan Listening Untuk Persiapan TOEFL ITP Pada Lembaga Bahasa - Suharti Sirajuddin (Yayasan Habiburrahman Jamalu Bina Ummat, 2022)
Mastery of English language skills has now become one of the demands of the job and It is to be one of a requirement for graduation. This ability must be proven by taking one of the international standardized English tests. One of the most common tests used in various educational institutions is the TOEFL ITP test. Where this test measures the level of understanding of participants in 3 forms of skills. This training is specifically in listening training where among the three skills in the TOEFL, listening skills are considered the most difficult skills for TOEFL ITP test participants. This training was held at the Language Institute of Megarezky University for a day with a total of 6 sessions. Where in each session participants were given an understanding of the TOEFL test in general, the pattern or form of the test, try outs, strategies and tips in each listening session on the TOEFL ITP test. The results of the training aimed at increasing the participants' TOEFL scores which were held the following day. The results of the test showed an increase in listening scores on the participants' TOEFL ITP scores